Integrating Lean and Operations Research to Reduce Waste in Food and Beverage MSMEs - A. Anas Haikal; Henry Hafidz Anbiya; Citra Dwi Kusumawardani (Indonesian Journal of Engineering, Science and Technology, 2026)
This study proposes a production optimization model for a multi-variant rice bowl micro, small, and medium enterprise (MSME) by integrating lean analysis and Mixed Integer Linear Programming (MILP). The problem addressed is raw material waste caused by differences in ingredient composition and discrete purchasing constraints. Data were collected from an MSME producing four variants: sweet spicy, sambal matah, opor, and black pepper. The collected data include raw material requirements, purchasing package sizes, minimum demand, and profit per product. Lean analysis was used to identify material waste, which was then incorporated into an MILP model to determine optimal production quantities while satisfying material and demand constraints. The model was solved using Microsoft Excel Solver with the Simplex LP method. The optimization results recommend producing 23 sweet spicy, 30 sambal matah, 25 opor, and 20 black pepper rice bowls. The proposed model reduces total material waste by 62.6% and generates a total profit of IDR 884,000. The findings indicate that integrating lean principles with MILP effectively improves production efficiency and reduces waste in multi-variant food production systems.. Keywords: Lean manufacturing; Mixed Integer Linear Programming (MILP); Production optimization; Material waste reduction; MSME food production.